Konsep Keputusan Nasabah dan Literasi Keuangan pada Lembaga Perbankan - Nurcahyo, Wiwit; Alamsyah, Agus Rahman; Dura, Justita (Magister Akuntansi Universitas Pancasila, 2023)
This study aims to identify whether the elements of service products, consumer choice, business location, education, and financial literacy have a significant influence on customer decisions at PT. BPR Putera Dana Malang. This study uses a quantitative methodological approach involving 100 respondents consisting of customers and prospective customers of PT. BPR Putera Dana Malang. The research findings show that the choice of consumers and the company's business location has a positive and significant influence on customer decisions. On the other hand, product and service elements have a negative and significant impact on customer decisions. In addition, education and financial literacy also have a positive and significant impact on customer decisions. The results of this study are expected to contribute to helping PT. BPR Putera Dana Malang in understanding the factors that influence customer decisions, as well as increasing understanding of the products and services offered as well as the level of financial literacy and can provide valuable insights for PT. BPR Putera Dana Malang in developing a more effective marketing strategy